Flood-tolerant rice improves climate resilience, profitability, and household consumption in Bangladesh. (December 2021) - Bairagi, Subir; Bhandari, Humnath; Kumar Das, Subrata; Mohanty, Samarendu
Highlights: Approximately 42% of the sampled farmers adopted Sub1 rice varieties in northwest Bangladesh. The main drivers of adoption are access to information on Sub1 rice through neighbors, farmer organizations, and training. Adoption of Sub1 rice increases rice yield (6.0% higher), profit (55.0% higher), and household consumption (15.0% higher). Non-adopters could be benefited if they adopted Sub1 rice—approximately 8%, 48%, and 15% more rice yield, profit, and consumption, respectively. Abstract: Climate change affects crop production through exposure to droughts, floods, pests, and pathogens. To mitigate climate-induced production losses, various stress-tolerant varieties have been developed and adopted in many countries around the globe. We assess the impacts of adopting submergence-tolerant (Sub1) rice varieties on productivity, profit, and rice consumption in northwest Bangladesh, using Endogenous Switching Regression and cross-sectional data in 2016. The findings reveal that the adoption of Sub1 rice had a significant positive impact on yield (6.0% higher), profit (55.0% higher), and rice consumption (15.0% higher) vis-à-vis the impact on non-adopters. Importantly, non-adopters could benefit if they adopted Sub1 rice—with about 8%, 48%, and 15% more rice yield, profit, and rice consumption, respectively. The findings further reveal that approximately 42% of the sampled farmers adopted Sub1 rice in northwest Bangladesh. The main drivers of this adoption are access to information on Sub1 rice through neighbors, farmer organizations, and training. Also, the application of pesticides and irrigation negatively affected the adoption of Sub1 rice. Finally, we find that rice production, profit, and rice consumption are location dependent. Therefore, we suggest implementing location-specific policies and developing social and institutional capacity to build trust in the new technology, which will increase the dissemination of Sub1 seeds by transferring agricultural knowledge and incentivizing farmers to adopt Sub1 rice in flood-prone areas in Bangladesh.